Molecular Iodine—An Expedient Reagent for Oxidative Aromatization Reactions of α,β-Unsaturated Cyclic Compounds - Malose Jack Mphahlele (Molecules, 2009)
Prompted by the scant attention paid by published literature reviews to the applications of molecular iodine in oxidative aromatization reactions, we decided to review methods developed to-date involving iodine as an oxidant to promote aromatization of α,β-unsaturated cyclic compounds.